Remarks on Trade Usages And Business Practices In International Sales Law - Graffi, Leonardo (Journal of Law and Commerce, 2011)
Trade usages and business practices are key elements of international commerce. In their day-to-day activities, traders and business people around the world constantly rely upon trade usages and business practices across a variety of industries. Usages and practices tend to be dignified by the business community with a status equivalent to that of actual law. As a matter of fact, many business persons often tend to regard trade usages and business practices as very powerful tools to ensure the stability of their bargain and, at times, transact business solely based on such usages and practices, without any written contract. Due to the importance of this subject, distinguished international legal commentators have often attempted to define trade usages and business practices and, in doing so, they have indeed succeeded at providing a substantial amount of theoretical ammunition for the benefit of the interpreter. What is more challenging, in my opinion, is to understand the interplay (and the related legal and commercial consequences) arising from the application of trade usages and business practices alongside the black letter rules of international conventions and model law instruments, which often refer to usages and practices without defining them.